Wileńska „szkoła” Manfreda Kridla. Przyczynek do rozważań na temat rodowodów naukowych Ireny Sławińskiej i Czesława Zgorzelskiego - Padło, Maria (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article is about the beginnings of of two researchers from The John Paul II Catholic University of Lublin – Czesław Zgorzelski and Irena Sławińska. It describes a Manfred Kridl’s integral method which inspired both scientists. The article includes the review of some Kridl’s publications and polemical texts. It also presents memories of professor shared by his students – Zgorzelski and Sławińska. In their publications, you can see the reference to Vilnius group’s conception.